التشاركية في التخطيط ألمديني والتصميم الدروس المستقاة من التجربة الألمانية في التخطيط لمرحلة ما بعد الحرب في سورية - غسان البدوان (Tishreen University, 2017)
This paper deals with participatory decision making and planning processes. It critically looks at methods and tools that are practiced currently in Germany and in particular in the city of Berlin, where the author has close relationship to and has studied in depth the Berlin experience made during the past decades. The process of public involvement that started in the 1970ies in Berlin and in the Federal Republic of Germany (BRD) is going to be monitored continiously. Focus is laid on the discourse on whom and how when to involve. Meanwhile the city of Berlin has developed a handbook on public participation that is briefly presented and assessed in this paper. Selected best practice cases where certain tools have been successfully applied in Berlin will be presented and analysed. This paper is meant to enlarge the knowledge about state of the art dicourse on participatory urban planning, design and implementation and gives a brief outlook on replicability of instruments for participatory urban planning and design in the Syrian context. تتعلق هذه الورقة البحثية بصنعواعتماد قرار المشاركة وعملية التنظيم من وجهة النظرة الناقدة للمناهج والأدوات المطبقة والتجارب الحديثة في هذا المجال في ألمانيا، وبشكل خاص في مدينة برلين، المدينة التي يرتبط بها الباحث خاصة بمجال البحث العلمي والعمل الجامعي بعلاقة عميقة، وقد رافق التطورات في هذا الاتجاه من وجهة النظر العلمية في السنوات العشر الماضية. لقد بدأ منهج المشاركة الأهلية في مدينة برلين/جمهورية ألمانيا الاتحادية منذ سبعينيات القرن الماضي وقد استمرت وتطورت هذه التجربة إلى يومنا هذا، حيث يتيح للقاطنين من خلال المشاركة في عملية التطوير والبناء المراقبة المتواصلة لسير عملية التطوير والبناء. في سياق هذه التجربة يطرح السؤال المهم: من يشارك في اتخاذ القرار وكيف يكون شكل هذه المشاركة ؟ لقد طورت الجهات المختصة في مدينة برلين كتيباً وأدوات بخصوص طرائق وأساليب ومناهج المشاركة الأهلية، والتي تعرض وتناقش وتقيم في هذه الورقة ويختار هنا أحد التجارب الناجحة في هذا المجال والتي استخدمت فيها بعض الأدوات، التي ساهمت في نجاح التجربة في مدينة برلين ولقد تعرضت الورقة لعرض وتحليل هذه التجربة. ويعطي البحث نظرة في إمكانية استخدام أدوات التنظيم ألمديني والتصميم في سياق الحالة السورية في مجال إعادة الإعمار.